ENHANCING GRADUATE EMPLOYABILITY IN THE MALAYSIAN CAPITAL MARKET - Mohd Dali, Nuradli Ridzwan Shah; Wan Nawang, Wan Rasyidah; Abdul Hamid, Hanifah; Misbah, Hanim; Nawai, Norhaziah; Johari, Fuadah; Mohd Noor, Mohd Nazri; Wan Mohamad Nazarie, Wan Nur Fazni; Mohd Soffian Lee, Umi Hamidaton (I-iECONS e-proceedings, 2023)
Higher education today has expanded and become more complex, where numerous degrees, training programs, and fields of study are offered. Additionally, the dynamic labour market has transformed remarkably, resulting in intense employment among graduates. The notion of graduate employability is becoming an increasingly important global issue. Employers now look for individual factors such as attitude, behaviours, and skills. Therefore, universities have gradually moved their focus on enhancing graduate employability. This paper examines how far the graduate employability program has achieved its target. The program involved 93 graduates of 2021 and 2022 from various local public universities taking the SCLE Modules 6 and 7 professional exams. The participants were required to attend a course and take an examination in this program. Sitting the Module 6 and 7 exams will enable the participants to get the professional license as Capital Market Service Representative License (CMSRL) through capital market participating organizations. The program started in June 2022 with four days of lectures from the industry, followed by six days of tutorial sessions, and finally sitting the exams in August 2022. Collaboration between university and industry can achieve the mission of bridging the academics ivory tower and industry labour market with the required skills.